Globalization, Democratization and Political Change in Malaysia (New Media And 2018 Elections) - Arizka Warganegara; Syarief Makhya; Denden Kurnia Drajat (Universitas Sultan Ageng Tirtayasa, 2019)
This is a study about the nexus relations among globalisation, democratisation process and its implication upon the political change in Malaysia. Malaysian internal politics is very dynamics and contentious as well as running based on the ethnic consensus. The result recent Malaysian election has changed the Malaysian political landscape. The 61 years regime of Barisan Nasional (BN) has been defeated by the opposition that led by former Malaysian Prime Minister, Mahathir Mohammad. By applying qualitative library research. The result shows that the globalisation has a direct impact on the Malaysian democratisation progress. It also, therefore, influences on creating a political change in Malaysia. This paper argues that globalisation and democratisation process became a trigger factor of new media development. The non BN-linked government media such as Malaysiakini.com and the Malaysian Insider play a significant role in distributing information related to the corruption scandal of BN elites, notably a corruption scandal of Najib Razak, a former Prime Minister of Malaysia.